A novel injectable fibromodulin‐releasing granular hydrogel for tendon healing and functional recovery. Issue 1 (14th July 2022) - Xu, Xue; Zhang, Yulong; Ha, Pin; Chen, Yao; Li, Chenshuang; Yen, Emily; Bai, Yuxing; Chen, Renji; Wu, Benjamin M.; Da Lio, Andrew; Ting, Kang; Soo, Chia; et al.
Abstract: A crucial component of the musculoskeletal system, the tendon is one of the most commonly injured tissues in the body. In severe cases, the ruptured tendon leads to permanent dysfunction. Although many efforts have been devoted to seeking a safe and efficient treatment for enhancing tendon healing, currently existing treatments have not yet achieved a major clinical improvement. Here, an injectable granular hyaluronic acid (gHA)‐hydrogel is engineered to deliver fibromodulin (FMOD)—a bioactive extracellular matrix (ECM) that enhances tenocyte mobility and optimizes the surrounding ECM assembly for tendon healing. The FMOD‐releasing granular HA (FMOD/gHA)‐hydrogel exhibits unique characteristics that are desired for both patients and health providers, such as permitting a microinvasive application and displaying a burst‐to‐sustained two‐phase release of FMOD, which leads to a prompt FMOD delivery followed by a constant dose‐maintaining period. Importantly, the generated FMOD‐releasing granular HA hydrogel significantly augmented tendon‐healing in a fully‐ruptured rat's Achilles tendon model histologically, mechanically, and functionally. Particularly, the breaking strength of the wounded tendon and the gait performance of treated rats returns to the same normal level as the healthy controls. In summary, a novel effective FMOD/gHA‐hydrogel is developed in response to the urgent demand for promoting tendon healing.